Resposta :
Resposta:
A) X - 7 = 0
X = 0 + 7
X = 7
B) X - 10 = 3
X = 10 + 3
X = 13
C)X + 4 = 7
X = 7 - 4
X = 3
D)X + 2 = 9
X = 9 - 2
X = 7
E)X - 1 = - 3
X = - 3 + 1
X = - 2
F) 2x - 7 = 9
2x = 9 + 7
2x = 16
x = 16 ÷ 2
x = 8
G) 7x = 4x +5
7x - 4x = 5
3x = 5
x = 5 ÷ 3
x = 1,66...
H) 5x +1 =36
5x = 36 - 1
5x = 35
x = 35 ÷ 5
x = 7
i) 5x + 21 = 10x + 13
5x - 10x = 13 - 21
- 5x = - 8
- x = - 8 ÷ 5
- x = - 1,6
x = 1.6
J)11x + 17 = 10x + 13
11x - 10x = 13 - 17
x = - 4
K) 3x + 1,6 = 0,6
3x = 0,6 - 1,6
3x = - 1
x = - 0,333...
Explicação passo-a-passo:
Espero ter ajudado :-)